Cell Proliferation as Assessed by Expression of Proliferating Cell Nuclear Antigen or the Uptake of Bromodeoxyuridine in a Rabbit Model of Leg-lengthening - Li, G.; Simpson, A. H. R. W.; Kenwright, J.; Triffitt, J. T. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
An experimental model of leg lengthening has been used to study the cellular responses of the regenerating bone to different rates of distraction. Cell proliferation were assessed by detection of proliferating cell nuclear antigen using a monoclonal antibody, PC10. The technique was verified by comparison with bromodeoxyuridine uptake and subsequent detection with specific antibody (Bu20A). The positive staining index (PSI) was calculated for a variety of tissues and the PC10 PSI was greater than that of Bu20A, as described by the expression: PC10 PSI = 1.6 Bu20A PSI + 12.9, with a correlation coefficient 0.79. The results suggest that PC10 may be used as an alternative marker to assess cell proliferation in rabbit regenerating bone tissue. In addition, the rate of cell proliferation during leg-lengthening was found to reach a maximum at a distraction rate of 0.7 mm/day without further change at higher rates.Cell proliferation was assessed in an experimental system of leg-lengthening by two separate methods. The presence of proliferating cell nuclear antigen or the uptake of bromodeoxyuridine were determined immuno-histochemically. Both methods indicated cell proliferation during leg-lengthening reaches a maximum at a distraction rate of 0.7 mm/day.
Keywords: Cell proliferation; immunohistochemistry; PC10; bromodeoxyuridine; rabbit model; leg-lengthening